2014
DOI: 10.1002/da.22299
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Application of Functional Neuroimaging to Individualized Treatment for Anxiety and Depression

Abstract: Functional neuroimaging has led to significant gains in understanding the biological bases of anxiety and depressive disorders. However, the ability of functional neuroimaging to directly impact clinical practice is unclear. One important method by which neuroimaging could impact clinical care is to generate single patient level predictions that can guide clinical decision-making. The present review summarizes published functional neuroimaging studies of predictors of medication or psychotherapy outcome in maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 91 publications
(267 reference statements)
1
38
0
2
Order By: Relevance
“…Although anxious youths exhibit heightened amygdala reactivity to threat (Killgore and Yurgelun-Todd, 2005;McClure et al, 2007b;Thomas et al, 2001), and one previous study demonstrated that greater amygdala predicted better treatment response in a small sample of anxious youth (McClure et al, 2007a), we did not find evidence that amygdala activation predicted treatment response. Prior studies using data-driven approaches have also failed to find amygdala activation as a significant predictor of response to treatment (Ball et al, 2014a), suggesting that pathophysiology, as reflected by abnormal patterns of brain reactivity, may not necessarily serve as predictors of treatment response.…”
Section: Predictors Of Treatment Response In Anxious Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Although anxious youths exhibit heightened amygdala reactivity to threat (Killgore and Yurgelun-Todd, 2005;McClure et al, 2007b;Thomas et al, 2001), and one previous study demonstrated that greater amygdala predicted better treatment response in a small sample of anxious youth (McClure et al, 2007a), we did not find evidence that amygdala activation predicted treatment response. Prior studies using data-driven approaches have also failed to find amygdala activation as a significant predictor of response to treatment (Ball et al, 2014a), suggesting that pathophysiology, as reflected by abnormal patterns of brain reactivity, may not necessarily serve as predictors of treatment response.…”
Section: Predictors Of Treatment Response In Anxious Youthmentioning
confidence: 99%
“…For example, anterior cingulate cortex (ACC) reactivity measured by functional magnetic resonance imaging (fMRI) has been shown to predict responses to pharmacological and psychotherapy treatment in depression (Ball et al, 2014a;Fu et al, 2013). In contrast, the existing literature on predictors of response to treatment in anxiety disorders is much smaller (Ball et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Functional neuroimaging measures may help achieve this goal. 1 For example, greater activity at baseline in the anterior insula or anterior cingulate cortex (ACC), measured with 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET), has been associated with a positive outcome from antidepressant medication in patients with major depressive disorder. 2,3 In the present study we tested whether resting-state functional connectivity (rs-fc) between the basolateral amygdala (BLA) and ventromedial prefrontal cortex (vmPFC) could predict outcome from cognitive behavioural therapy (CBT) in patients with obsessive-compulsive disorder (OCD).…”
Section: Introductionmentioning
confidence: 99%
“…4 There have been several attempts to correlate functional neuro imaging measures and CBT outcomes in patients with OCD. 1,5 Initial studies focused on cortico-striato-thalamo-cortical regions believed to be involved in the pathophysiology of OCD, such as the orbitofrontal cortex (OFC). Indeed, findings from studies using FDG-PET or single-photon emission computed tomography (SPECT) suggest that greater baseline OFC activity in patients with OCD is associated with a positive outcome from CBT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation